XIAP Limits Autophagic Degradation of Sox2 and Is A Therapeutic Target in Nasopharyngeal Carcinoma Stem Cells - Ji, Jiao; Yu, Yan; Li, Zhi-Ling; Chen, Ming-Yuan; Deng, Rong; Huang, Xiang; Wang, Guang-Feng; Zhang, Meng-Xia; Yang, Qi; Ravichandran, Senthilkumar; Feng, Gong-Kan; Xu, Xue-Lian; et al. (Theranostics, 2018)
Nasopharyngeal carcinoma (NPC) is the most frequent head and neck tumor in South China. The presence of cancer stem cells (CSCs) in NPC contributes to tumor maintenance and therapeutic resistance, while the ability of CSCs to escape from the apoptosis pathway may render them the resistant property to the therapies. Inhibitor of apoptosis proteins family proteins (IAPs), which are overexpressed in nasopharyngeal carcinoma stem cells, may play an important role in maintaining nasopharyngeal cancer stem cell properties. Here, we develop a novel CSC-targeting strategy to treat NPC through inhibiting IAPs. Human NPC S-18 and S-26 cell lines were used as the model system and . Fluorescence activated cell sorting (FACS) assay was used to detect nasopharyngeal SP cells and CD44+ cells. The characteristics of CSCs were defined by sphere suspension culture, colony formation assay and cell migration. The role of XIAP on the regulation of Sox2 protein stability and ERK1-mediated phosphorylation of Sox2 signaling pathway were analyzed using immunoblotting, immunoprecipitation, immunofluorescence, phosphorylation mass spectrometry, siRNA silencing and plasmid overexpression. The correlation between XIAP and Sox2 in NPC biopsies and their role in prognosis was performed by immunohistochemistry. APG-1387 or chemotherapies-induced cell death and apoptosis in S-18 and S-26 were determined by WST, immunoblotting and flow cytometry assay. IAPs, especially X chromosome-linked IAP (XIAP), were elevated in CSCs of NPC, and these proteins were critically involved in the maintenance of CSCs properties by enhancing the stability of Sox2. Mechanistically, ERK1 kinase promoted autophagic degradation of Sox2 via phosphorylation of Sox2 at Ser251 and further SUMOylation of Sox2 at Lys245 in non-CSCs. However, XIAP blocked autophagic degradation of Sox2 by inhibiting ERK1 activation in CSCs. Additionally, XIAP was positively correlated with Sox2 expression in NPC tissues, which were associated with NPC progression. Finally, we discovered that a novel antagonist of IAPs, APG-1387, exerted antitumor effect on CSCs. Also, the combination of APG-1387 with CDDP /5-FU has a synergistic effect on NPC. Our study highlights the importance of IAPs in the maintenance of CSCs in NPC. Thus, XIAP is a promising therapeutic target in CSCs and suggests that NPC patients may benefit from a combination treatment of APG-1387 with conventional chemotherapy.